Evaluating the efficacy of liposomal delivery of nedaplatin in enhancing cytotoxicity, genotoxicity and DNA damage in lung, breast, and osteosarcoma cancer cell lines - Abdelnaser, Salma (AUC Knowledge Fountain, 2018)
Today, cancer is the second leading cause of death worldwide where chemotherapy is one of the common strategies to control it. Platinum-based chemotherapeutic drugs (PBDs) are a mainstay in chemotherapy due to their high effectiveness in a wide spectrum of cancer types. Severe toxicity and innate or acquired drug resistance are the two main problems limiting PBD clinical use. One approach to overcome both problems is by employing cancer-targeting drug delivery systems where liposomes, in particular, are gaining much attention in oncology application and have established superior potency compared to the corresponding free drugs in clinical application already. This study aims to evaluate the cytotoxicity of liposome-encapsulated nedaplatin, a second generation platinum-based anticancer drug which is clinically available and heavily used in Japan only thus far, in comparison to its non-encapsulated free form in three cancer cell lines; non-small cell lung cancer A549, breast cancer MCF7 and osteosarcoma U2OS. The novel liposome was designed and produced in the Chemistry department at The American University in Cairo and showed promising physicochemical properties which were found to be reflected biologically. We evaluated cytotoxicity using different approaches including MTT, live cell counting, clonogenic survival assay and Cytokinesis Block Proliferation Index (CBPI) assay, all showing statistically significant superior anti-proliferative effects for liposomal nedaplatin. Genotoxicity in terms of chromosomal damage assessed through micronucleus formation fold changes and DNA damage in the form of DNA double-strand breaks (DSBs), the most deleterious type of DNA damage and one known to be induced by PBD-DNA interstrand crosslinking, supported superior activity of liposomal nedaplatin from which it was inferred that the liposomal formulation demonstrated successful drug delivery to the molecular target, DNA, achieving good drug release and expected cellular distribution. Nedaplatin was shown to induce cell death through apoptosis in the 3 cell lines as demonstrated in nuclear morphological changes and pre-apoptotic marker signals identified by immunofluorescent staining for gH2AX.